Penerapan Asas Legalitas dalam Penjatuhan Sanksi Pidana Atas Masyarakat Adat - Fasih Arrizall (Universitas Medan Area, 2021)
In Indonesian, the main source of criminal law is in the Criminal Code and other Criminal laws and regulation. However, it is possible that customary law is considered as the source of law with certain limitations. This study aims to determine and analyze application of criminal sanctions to indigenous people and relevance of the legality of criminal law to customary law sanctions. The methodology used is juridical normative research method using a statutory and conceptual approach. With this research, the finding or conclusions are obtained that application of sanctions to customary law communities is recognized by several communities, and they believe that the customary court is a legal system that is still used by some indigenous peoples, and stipulation of customary criminal law sanctions is often not in accordance with the principle of legality which based on the principle and norms of criminal law as stipulated in the revisions of Article 1 Paragraph (1) of the Criminal Code. Therefore, in conclusion, the application of legality principle in imposition of criminal sanction to customary society still benchmark the customary law within the society itself.